THE IMPACT OF ENGLISH SONG TOWARD PRONUNCIATION OF EFL LEARNERS IN ENGLISH AND LITERATURE DEPARTMENT UIN ALAUDDIN MAKASSAR - Harjulaini J, Leni; Maharani, Sardian; Surya, Waode (FKIP Universitas Khairun, 2025)
This study investigates the impact of English songs towards pronunciation skills among EFL learners in the English and Literature Department at UIN Alauddin Makassar. A descriptive quantitative design was used with an initial survey of 56 third semester students, from which 28 participants were purposively selected based on their consistent use of English songs as a learning tool. Drawing on theoretical frameworks by Kelly (2000) and Djiwandono (2008), the study hypothesized that musical repetition and natural intonation improve articulation and fluency. Two lines of discussion emerged: first, an evaluation of students’ pronunciation levels revealed significant improvements from pretest to posttest; second, both statistical analysis and qualitative feedback underscored the substantial impact of English songs in promoting better pronunciation. These findings support the integration of song-based activities into traditional language instruction as a dynamic method to enhance language acquisition and pronunciation accuracy.